Incorporating medical students into school-based asthma education improves asthma knowledge in children. (3rd October 2021) - Kearney, Jessica; Everson, Lucy; Coppel, Jonny; Braithwaite, Simon; Gibson, Lucy; Anderson, Bliss; George, Daniel; Cahilog, Zhen; Chodhari, Rahul
Abstract: Objectives: Asthma affects 1.1 million children in the UK, substantially impacting quality of life and leading to significant morbidity and mortality. Effective asthma self-management, education and empowerment can lead to a reduction in asthma related morbidity and mortality. We hypothesized that medical students can significantly improve school children's knowledge and awareness of asthma, at least in the short term. We sought to implement a medical student-led educational intervention program tailored to school-aged children, measure immediate improvements in asthma-related knowledge among participants, and determine if any population factors were associated with a difference in knowledge improvement. Methods: Children were recruited from schools in Greater London. A 20-minute presentation was given by medical students which covered basic physiology of asthma, triggers, treatment, how to recognize a peer who is having an acute asthma attack and common misconceptions about asthma. The children's knowledge was tested using questionnaires completed before and immediately after the presentation. Results: Medical students taught 1711 children aged 5 to 11 both with and without asthma. The average questionnaire score was 4.67/13 (SD 2.82) at baseline and 10.15/13 (SD 2.92) following the program. An improvement in scores was observed in all age groups and was greatest in children aged 10 and 11 ( p  = 0.016 and 0.049 respectively). Conclusion: We successfully implemented a medical student led asthma education program for school aged children in the UK. This novel approach was well received and led to a significant improvement in asthma knowledge amongst participants.